2015
DOI: 10.1016/j.ijwd.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Nail changes in female pemphigus vulgaris patients on immunosuppressive therapy

Abstract: BackgroundPemphigus vulgaris (PV) patients receiving immunosuppressive therapy may develop nail alterations resulting from infection, skin disorder, or drug regimen.ObjectiveThis study aims to describe nail changes in PV female patients receiving immunosuppressive therapy and to report the frequency of associated fungal and bacterial growth in the patients’ nails.MethodsTwenty-five female PV patients who had at least one acquired finger or toenail abnormality and had been administered at least one immunosuppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, 12% of already treated PV patients in Thai study, were found to have concomitant clinical onychomycosis (although only 5% were confirmed by mycological culture) ( 53 ). Similarly, an Egyptian study on PV female patients on immunosuppressive treatment also indicated 24% prevalence of onychomycosis, yet also 24% prevalence of bacterial periungual infection ( 54 ). What is worth noticing, fungal, and bacterial infection may mimic PV nail apparatus lesions and pose a threat to immunocompromised patients if left untreated, especially considering additional immunosuppressive treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, 12% of already treated PV patients in Thai study, were found to have concomitant clinical onychomycosis (although only 5% were confirmed by mycological culture) ( 53 ). Similarly, an Egyptian study on PV female patients on immunosuppressive treatment also indicated 24% prevalence of onychomycosis, yet also 24% prevalence of bacterial periungual infection ( 54 ). What is worth noticing, fungal, and bacterial infection may mimic PV nail apparatus lesions and pose a threat to immunocompromised patients if left untreated, especially considering additional immunosuppressive treatment.…”
Section: Discussionmentioning
confidence: 94%
“…A study by Schlesinger et al [6] noted nail changes in 47% (30 of 64) of patients with PV. Another study by El-Komy et al [7] on 25 patients with PV showed onycholysis and subungual hyperkeratosis in 16 patients (64%) as the most common nail alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Nail disease can be a part of the initial presentation along with mucosal and cutaneous lesions, can precede a flare of the pre-existing disease, or can be the only sign of the disease [5,6,7,8,9,10,11,12,13]. It manifests as chronic paronychia, onychomadesis, Beau's lines, trachyonychia, onycholysis, subungual hemorrhage, nail plate discoloration, pitting, onychoschizia, and nail dystrophy [6,7,8,9,10,11,12,13,14,15,16,17,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professor Murrell has always been an inspiration to us as a devoted mother and wife, an excellent clinician, a great mentor, a dedicated researcher, and a passionate traveler. Both the International Journal of Women’s Dermatology and the Women’s Dermatologic Society owe a debt of gratitude to Professor Murrell for her 8 years of service to the organization in the role of Founding Editor and co-Editor in Chief, for the creative energy that she invested in developing articles for the journal, 2 16 and for her solicitation of articles from world-renowned experts 17 30 that have improved the lives of women and their families throughout the world with blistering diseases.…”
mentioning
confidence: 99%